GROWTH AND YIELD OF PECHAY (Brassica rapa L.) WITH VARYING LEVELS OF GOLDEN SNAILS AMINO ACID - MARINA C. TADO (Western European Studies, 2023)
This study was conducted to determine the growth and yield of pechay with varying levels of golden snails amino acid (GSAA) on a farm lot within the school premises of Alangalang Agro-Industrial School, Alangalang, Leyte. The research was laid out using Randomized Complete Block Design (RCBD) for a single factor experiment with five (5) treatments and three (3) replications. T1 (100% chicken manure) which serves as the control, T2 (75% chicken manure and 25% GSAA), T3 (50% chicken manure and 50% GSAA), T4 (25% chicken manure and 75% GSAA) and T5 (100% GSAA). Results showed that after ten (10) days from transplanting no significant differences were observed on plant height, width of leaves, length of leaves and number of leaves. Similar observations were noted after 20 days from transplanting. However, after 30 days from transplanting or at harvest time, it was recorded that except for the number of leaves, pechay applied with the 100% percent chicken manure produced the highest mean in terms of plant height, width of leaves, and length of leaves. Significant differences were also recorded in the yield of pechay.
Keywords: Pechay; Golden Snails Amino Acid; Growth and Yield